Evaluation of GaN Power Transistor Switching Performance on Characteristics of Bidirectional DC-DC Converter - Frivaldsky, Michal; Morgos, Jan; Zelnik, Richard (Elektronika ir Elektrotechnika, 2020)
The paper deals with the experimental analysis of the switching performance of selected GaN (Galium Nitride) power transistor, whose use is then expected in bidirectional buck/boost DC-DC converter. The switching performance was evaluated through highly accurate and verified simulation models of GS61008P transistor from GaN systems. Experiments have been provided for a wide spectrum of switching frequency and load current in order to verify transistor performance. Then, based on the results, it was expected that high-frequency operation (above 500 kHz) should not distort the efficiency performance of the designed bidirectional converter. This was confirmed after laboratory measurements of the efficiency of the proposed DC-DC converter, while operation under very high switching frequency was more effective compared to low-frequency operation. Over 95 % of efficiency was achieved for both buck and boost mode (125 W), even switching frequency was above 500 kHz.